"The obligations of the notary and their impact on fulfilling their civil responsibility (a comparative study) " - AbdulHaleem Ibrahim , Researcher. Ibrahim; Ressan Jadder, Prof. Dr. Ghani (Basra studies journal, 2023)
The civil responsibility of a notary is realized as long as there are many obligations placed on him during his professional career, especially considering the close link between him and those dealing with him, as he is a place of trust and a witness to their actions, entrusted with their secrets. However, individuals, in general, are not aware of all the obligations of the notary, and a breach of any of them leads to the realization of his civil responsibility. He is obligated to consider the legal situations defined by the legislator while adhering to the ethical obligations imposed on him by practical reality. This is a result of the penetration of his work among the members of society, aiming to be a trustworthy figure capable of perpetuating the essence of his authentic work. The human desire for justice is linked to the continuous development of society, reflecting the need to regulate individuals' behaviors within the framework of the law. Therefore, a notary may overlook following the legal procedures and implementing what should be executed, leading to mistakes that trigger the responsibility that is only realized if it becomes a violation of one of his obligations, whether intentional or a result of negligence. Various cases can be examined to establish the civil responsibility of the notary, whether occurring before or after the notarization process. If an error arises that violates any of these obligations, the affected party, whether related or unrelated, has the right to seek compensation by filing a civil responsibility lawsuit against the notary.